BARBOUR, J. Murray and KUTTNER, Fritz A. 1. Meantone Temperament in Theory and Practice. 2. The Theory and Practice of just Intonation. Musurgia Records (P.O. Box 242, Jackson Heights 72, New York, USA). Theory Series A, Nos. 2 and 3. Each 2 s. 12 in. 33-1/3 r.p.m. S (US) 8.75 and 9.25. (International Library of African Music, 1959)
pages: 97-98
Keywords: African Music